Implementation of The Independent Curriculum in Enhancing Critical Thinking Skills of Senior High School Students in Bandar Lampung - Herlisya, Destia (International Journal Corner of Educational Research, 2025)
This study was motivated by the imperative to strengthen critical thinking as a core competence within the Kurikulum Merdeka and by evidence that its implementation across senior secondary schools in Bandar Lampung remains uneven. The research focused on analysing how the Curriculum Merdeka contributes to the development of students’ critical thinking skills by examining classroom practices, teacher and student perceptions, and facilitating and inhibiting factors. A qualitative descriptive approach with purposive sampling was employed in three senior secondary schools (two public, one private), involving teachers, students and school leaders. Data were collected through semi-structured interviews, participant observation and document analysis (lesson plans and student artefacts) and were thematically analysed using Miles and Huberman’s framework, with source triangulation and member checking to strengthen validity. Findings indicate that the Kurikulum Merdeka creates opportunities for project-based and discussion-centred learning that can foster critical thinking, but its effectiveness is contingent upon teacher readiness, instructional leadership, infrastructure provision and students’ dispositions. The study recommends sustained pedagogical training, systematic institutional support and interventions to enhance student engagement and confidence; these measures carry implications for local policy and school practice in realising the Pelajar Pancasila profile.